2016
DOI: 10.1111/rda.12764
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between endometritis and oxidative stress in the follicular fluid and luteal function in the buffalo

Abstract: In this study, alteration in the follicular fluid composition and luteal function was investigated in the buffalo with endometritis. Genitalia were classified into cytological and purulent endometritis on the basis of polymorphonuclear cell cut off while non-endometritis served as control (n = 10/group). In the follicular phase, the number of surface follicles was counted, diameter of the largest follicle was measured and the follicular fluid was assayed for total protein, cholesterol, malondialdehyde (MDA), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Therefore, the normal function of GCs is crucial to the growth, development, and maturation of oocytes (Yamamoto et al, 2015;Guo et al, 2016). Existing studies showed that the follicular development potentially decreased, the apoptotic rate of GCs increased, and the changes in follicular microenvironment and endocrine occurred in EM-related infertility (Gupta et al, 2008;Behera et al, 2016). Poor quality of oocytes might be closely related to GCs in follicles in patients with EM-related infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the normal function of GCs is crucial to the growth, development, and maturation of oocytes (Yamamoto et al, 2015;Guo et al, 2016). Existing studies showed that the follicular development potentially decreased, the apoptotic rate of GCs increased, and the changes in follicular microenvironment and endocrine occurred in EM-related infertility (Gupta et al, 2008;Behera et al, 2016). Poor quality of oocytes might be closely related to GCs in follicles in patients with EM-related infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of the innate uterine defence mechanism to eliminate the bacteria by 3 weeks PP increases the risk of endometritis. In the buffalo, the incidence of PP endometritis is reported to be 20%, and subclinical endometritis (SE) is a major problem (Behera et al, ; Rao & Sreemannarayana, ). Escherichia coli (E. coli), main pathogen isolated from SE, carries pathogen‐associated molecular patterns (PAMP) like lipopolysaccharide (LPS) that are recognized by the pattern recognition receptors (PRR) like toll‐like receptors (TLR) of the host.…”
Section: Introductionmentioning
confidence: 99%